Efektivitas Metode Pembiasaan Terhadap Pembentukan Karakter Religius Siswa Kelas VII MTs Model Ihsaniyah Kota Tegal - Wulan Mulyana; Arif Muntaqo (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2022)
This research is motivated by the low attention of schools to the religious character of students. In the age of advanced technology, many students are swayed by various kinds of information and content on free social media so that students cannot sort out which things are good and which things are bad for their character. The interesting thing is that in MTs Model Ihsaniyah Tegal always applies the habituation method every day before learning with the aim of shaping student character. This study used a quantitative approach with an experimental method with a pre-experimental research design type one group pretest-postest design. The sample of this research was all seventh grade students at MTs Model Ihsaniyah Tegal with a total of 43 people. The results of this study are: (1) The application of habituation method in MTs Model Ihsaniyah Tegal City is classified as sufficient. This is evident from the posttest results of seventh grade students there is an increase in student character building, that there are 23 students with a percentage of 53.5% who are in the category of always applying the habituation method, and 20 students with a percentage of 46.5% who are in the category of often applying the habituation method. (2) The religious character of seventh grade students at MTs Model Ihsaniyah is classified as sufficient. This is evident from the average results of the pretest assessment of religious character before treatment is 25.86 and the average results of the posttest assessment of students' religious character after treatment is 32.60. (3) The habituation method is effective on the formation of religious character of seventh grade students at MTs Model Ihsaniyah Tegal City. This is evident from the results of research showing that t0 is greater than tt at the 5% significance level comparing the magnitude of